1987
DOI: 10.1089/aid.1987.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Chemical Analysis of P6, the Carboxyl-Terminal Fragment of HIV P15

Abstract: The first open reading frame of the HIV genome has been identified as the gag gene. The proteins encoded by this gene are p17 as the amino-terminal protein, p24 as the middle peptide, and p15 as the carboxyl-terminal end. A monoclonal antibody recognizing an antigenic determinant on a fragment of p15 has been developed and designated M35/2F8. This monoclonal has been instrumental in radiosequencing the carboxyl-terminal product of p15, p6, and in determining the cleavage site between this protein and the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…analyses suggested that the C-terminal domain of Gag, which is processed in NCp7 and p6 (15), could interact with Vpr. Moreover, both the C and the N termini of Vpr were reported to be necessary for the incorporation of this protein in the virus particles (10,24,25).…”
Section: In Vitro Interactions Of Vpr With Ncp7 But Not P6 and Importmentioning
confidence: 99%
See 2 more Smart Citations
“…analyses suggested that the C-terminal domain of Gag, which is processed in NCp7 and p6 (15), could interact with Vpr. Moreover, both the C and the N termini of Vpr were reported to be necessary for the incorporation of this protein in the virus particles (10,24,25).…”
Section: In Vitro Interactions Of Vpr With Ncp7 But Not P6 and Importmentioning
confidence: 99%
“…The involvement of NCp7 in Vpr encapsidation would raise the question of the coexistence of NCp7-Vpr complexes with those resulting from the binding of genomic RNA to the nucleocapsid domain of Gag, a process known to be critical for RNA packaging (15,18). Fluorescence and NMR studies have shown that the zinc finger domains of NC proteins participate in the RNA binding (40,41), a finding supported by the observed reduction in RNA packaging of HIV-1 mutants with defects in the structure of the zinc fingers (37)(38)(39).…”
Section: Fig 6 Ratio Of Virion-incorporated Vprmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage of HIV-1 Pr55m by the viral protease occurs during virion formation and yields the major core proteins-namely, matrix (MA), capsid (CA), and nucleocapsid (NC) proteins with molecular masses of 17 (p17), 24 (p24), and 7 (p7) kDa, respectively (7). Additionally, a 6-kDa proline-rich C-terminal protein, p6, is generated (8). While cleavage of HIV-1 Pr55m8 is necessary for the production of infectious virions, it is not required for budding to occur, as shown by viral protease inhibitor (9) and mutagenesis studies (10).…”
mentioning
confidence: 99%
“…A role for the C terminus of HIV-1 gag in virion assembly is suggested by mutagenesis studies in which C-terminal truncations of Pr55m prevent particle formation (8,(17)(18)(19). We theorized that these truncations may inhibit particle formation through abrogation of gag membrane association.…”
mentioning
confidence: 99%